1988
DOI: 10.1590/s0074-02761988000400008
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la frequencia alimentaria sobre algunos parametros poblacionales de Rhodnius neivai

Abstract: After changing feeding frequency to a weekly and biweekly basis, a statistical evaluation of the variation of some population and reproductive parameters was conducted. It was based on four cohorts experiments of Rhodnius neivai fed on hen or rabbit. We found a direct relationship between blood feeding frequency and the parameters adult average longevity, maximum longevity and life expectancy in the animals fed on hen. On the other hand, in the insect fed biweekly on rabbit, these three values were higher than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The estimated frequencies would correspond to the optimal frequencies reported by Cabello et al (1988). These figures are also comparable with those reported for R. prolixus: between 0.089 and 0.119 bites/insect/day [periods between bites from 8.4 to 11.2 days (Rabinovich et al 1979)].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The estimated frequencies would correspond to the optimal frequencies reported by Cabello et al (1988). These figures are also comparable with those reported for R. prolixus: between 0.089 and 0.119 bites/insect/day [periods between bites from 8.4 to 11.2 days (Rabinovich et al 1979)].…”
Section: Discussionsupporting
confidence: 85%
“…From the curves of the decrease in weight, times Td = 36 and Td = 26 days to a negative outcome of weight were estimated for T. infestans and M. spinolai respectively. These values suggest critical frequencies (sensu Cabello et al 1988) of 0.028 and 0.038 bites/insect/day for these species. Below these values, vital parameters would be depressed.…”
Section: Discussionmentioning
confidence: 82%
“…Comparing cohorts fed on rabbits or on hens ( Gallus sp. ), Cabello et al (1988) found that life expectancy and survival were higher in insect cohorts fed on rabbits. In this study, we compared rodent vs. rabbit as host, and our results showed a remarkable effect of rabbit on insect fecundity, but not on average weight or survival.…”
Section: Discussionmentioning
confidence: 99%
“…The triatomines were fed on non-infected laboratory mice ( Mus musculus ) at day 30 post-infection. We determine the refeeding day, considering the highly variable feeding frequency of triatomines in nature, ranging from months of fasting to daily intake (Cabello et al, 1988), and considering the effect of fasting on parasite survival (Kollien & Shaub 2000). After the experimental period, the insects were euthanized by freezing for a minimum of 48 hours following the bioethical protocol (N° 19262- MED-UCH).…”
Section: Methodsmentioning
confidence: 99%